Alloying of ohmic contacts to n-type 4H-SiC via laser irradiation - Hürner, Andreas; Schlegl, Thomas; Adelmann, Benedikt; Mitlehner, Heinz; Hellmann, Ralf; Bauer, Anton; Frey, Lothar (2013)
In this study, we present results on alloying nickel as ohmic contact material to n-type 4H-SiC via a continuous wave fiber laser with different laser beam powers and processing times. The laser system exhibits an emitting wavelength of 1070 nm and a beam propagation factor M smaller than 1.1. Contact resistance was determined by current-voltage measurement using two- terminal contact resistance method. The results indicate that a laser beam power of at least 100 W is mandatory to initialize contact silicidation. Although the contact resistance is improvable by longer processing times, our experiments outline the much higher impact of laser beam power to contact silicidation compared to processing time. For laser beam powers of 300 W and processing times of 0.5 s a contact resistance of 6.5 ω comparable to contacts alloyed in a lamp heated furnace at 910 °C for 2 min with a contact resistance of 10.3 ω, was achieved. © (2013) Trans Tech Publications, Switzerland.
Keywords: Back-side metallization; Contact resistance; Laser; N-type 4H-SiC; Nickel; Ohmic

Back side ablation of SiC diodes using a q-switched NIR laser - Adelmann, Benedikt; Hürner, Andreas; Roth, Gian-Luca; Hellmann, Ralf (Journal of Laser Micro Nanoengineering, 2015)
We study pulsed fiber laser back side ablation of silicon carbide diodes. With the objective to thin the SiC substrate thickness without damaging the semiconductor device or altering its electrical characteristics, we investigate the ablation characteristics of silicon carbide and determine the ablation threshold, rate and quality as well as the material composition at the ablated surface. Based on optimized process parameters, including track distance, laser repetition rate and scanning velocity, we micro structure the substrate of SiC diodes and compare its electrical characteristic to an unprocessed device. Our results prove that the typical diode characteristic and built-in voltage are not affected by the laser ablation process. Fiber laser back side ablation therefore offers a precise and efficient micro structuring approach for substrate thinning in silicon carbide technolog
Keywords: Laser ablation; Fiber laser; SiC diode; Serial resistance

Comparative study of n-LIGBT and n-LDMOS structures on 4H-SiC - Häublein, Volker; Temmel, Gerhard; Mitlehner, Heinz; Rattmann, Gudrun; Strenger, Christian; Hürner, Andreas; Bauer, Anton; Ryssel, Heiner; Frey, Lothar (2013)
N-LDMOS and n-LIGBT structures were manufactured with the same dimensions on a 4H-SiC wafer in order to allow for a direct comparison. The comparison of the devices includes output and transfer characteristics, blocking characteristics, and temperature behavior. © (2013) Trans Tech Publications, Switzerland.
Keywords: 4H-SiC; Bipolar; LDMOS; LIGBT; SiC devices; Unipolar